“METHODOLOGY OF THE DISSERTATION RESEARCH” AS AN ACADEMIC DISCIPLINE - Boris A. Yakimovich; Sergey G. Seletkov (Высшее образование в России)
In the article the authors examine ways of improving the quality and effectiveness of scientific qualification works of undergraduates and postgraduates. Develop training of undergraduates and graduate students in the methodology and presentation of thesis proposed by the introduction of appropriate discipline in the educational programs of graduate and postgraduate studies.